Implementation of a developed water tunnels cleaning model with an automatic sensing and operation mechanism - Yasen Abd, Rasha; Sachit Kaittan, Ali; Ali Mejeed, Raghad (International Journal of Engineering and Technology, 2020)
Iraq contains two main rivers with several sub streams and tributaries. One of the most important problems in these streams and tributaries is the amount of waste on the water surface. This waste can lead to many issues such as diseases infection and affects the fisheries. River cleaning machine is one of the most important solutions for this problem. In this paper, a developed cleaning machine was designed based on Arduino and remote sensing mechanism to reduce the operation time and cost. The proposed cleaning machine model was tested and validated and can be used efficiently in many places under different conditions.Â Â